Balancing choice and socioeconomic realities: analyzing behavioral and economic factors in social oocyte cryopreservation decisions - Gonen, Limor Dina (Frontiers in Endocrinology, 2024)
PurposeThis research investigates the influence of personal income, the likelihood of pregnancy from cryopreserved oocytes, and the risk of infertility, on the decision-making process of women. The study employs the economic stated preference framework alongside the Theory of Planned Behavior in order to comprehend the process of decision-making.Design/methodology/approachThe data had been collected from women between the ages of 18 and 65 via questionnaire employing conjoint analysis (CA). Through the utilization of this methodology, the factors influencing women’s choices concerning oocyte cryopreservation were quantified.FindingsThe study identified crucial factors that impact the determination to cryopreserve oocytes, such as personal financial resources, the likelihood of achieving a successful pregnancy using frozen oocytes, and the potential for infertility. The analysis reveals that a considerable number of participants perceive cryopreservation as a feasible alternative for augmenting their prospects for future procreation.Research implicationsThe results validate the patterns and the ways in which personal and socioeconomic elements impact choices regarding fertility. This has the potential to inform forthcoming health policies and educational initiatives that aim to provide more comprehensive support for women’s fertility decisions.Social implicationsThe research highlights the necessity of policy and societal support for women who are contemplating oocyte cryopreservation. It is recommended that public health policies incorporate provisions for state financing of cryopreservation in order to safeguard reproductive autonomy and alleviate the fertility risk linked to the aging process.Originality/valueHis research is unique in that it employs the Theory of Planned Behavior and an economic stated-preference framework to analyze the dynamics of oocyte cryopreservation decisions. This work enhances the existing body of literature by drawing attention to the socio-economic persona factors that influence choices regarding fertility preservation.